A Mixed-Method Approach on the Evolution of Influencer Marketing and Its Ethical Consideration in UAE - Mushtaq, Saleem; Shameem, Beenish; Alzoubi, Haitham M.; Al Kurdi, Barween; Joghee, Shanmugan; Hamadneh, Samer (International Review of Management and Marketing, 2025)
The paper aims to identify the evolution of influencer marketing along with ethical considerations taken in terms of celebrity endorsement. The research also considers ethical considerations, like “transparency and cultural sensitivity,” as vital to successful influencer collaborations. This literature investigates the “evolution of influencer marketing” in the UAE, emphasising the change from celebrity confirmations to micro-influencers. It discovers the role of social media along with the influencer in determining purchasing decisions for the products. The review also classifies gaps in research regarding the influence of local cultural nuances and regulatory frameworks on “consumer behaviour and brand loyalty” in the influencer marketing scenery. The research study employs a mixed-method approach, mixing “quantitative surveys and qualitative interviews,” to discover personalized influencer marketing’s influence in the UAE. It measures consumer perceptions regarding awareness, data privacy, trust, and ethical practices, pointing to uncover key understandings that inform marketing strategies and regulatory frameworks in the area. Based on the findings from the data collected, customers are attracted to influencer marketing even in the UAE where several ethical considerations and regulations have been used. It is used to maintain data privacy, cultural sensitivity, and even transparency in influencer marketing.